"Reference waters" in French laboratories involved in tritium monitoring: how tritium-free are they?. Issue 2 (23rd May 2014) - Fourré, E.; Jean-Baptiste, P.; Dapoigny, A.; Ansoborlo, E.; Baglan, N.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents a comprehensive survey of the tritium content of "reference waters" in real working conditions by French laboratories involved in environmental monitoring. Reference waters are virtually tritium-free waters used to determine blanks for the analytical system and to check for any contamination. It is therefore crucial to be sure of the low tritium content of these waters as this can limit the sensitivity and accuracy of the measurements. Water from the commercial brand "Abatilles" is widely used in French laboratories and nine samples were analyzed in this study. Three samples from other deep aquifers were also included. The results all range from 0.004 ± 0.004 Bq/kg to 0.175 ± 0.011 Bq/kg, well below the 0.5 Bq/kg advised by the French Safety Authority. The spread of the results can mainly be attributed to contamination through plastic during bottle storage. As expected, two samples from demineralized tap water showed higher tritium activities (0.3–0.35 Bq/kg). Both waters are suitable as reference water for routine monitoring (DL of about 10 Bq/kg) but should be used with caution for activities in the Bq/kg range.